English Department Students’ Metacognition Awareness in Completing Mini-thesis - Arjulayana, Arjulayana; Lastari, Dyah Supraba; Al-Manar, Abduh (Journal of English Education and Teaching, 2024)
This paper investigated the metacognition of final semester students in completing their mini-thesis. The obstacles faced by English study program students in writing mini-thesis were assumed resulted from their lack of metacognition implementation. Metacognition is often described as knowledge and control over one’s cognitive processes. This research used mixed-method design. The instruments used were observation, interviews, and questionnaire. The subjects of this research consisted of 18 students of 8th, 9th as well as graduated students and 10 lecturers of English Study program of Universitas Muhammadiyah Tangerang. This study showed: firstly, students are quite hard to complete mini-thesis due to their strategy following the schedule is need to be pushed by their advisors. Secondly, most respondents have good metacognitive awareness, while few of eighth and ninth semester students need to improve planning, information management strategy and monitoring. Thirdly, metacognition can be the effective solution to encourage students in achieving their target.